The comparative breeding biology, feeding ecology and bioenergetics of Adélie and Chinstrap penguins - Lishman, G (1983)
Adélie Pygoscelis adeliae and chinstrap P. antarctica penguins are the two most numerous Antarctic seabird species and play a major role as consumers in the marine ecosystem. Their ecological adaptations to breeding and feeding and influence on marine resources at Signy Island, South Orkney Islands were examined during the 1980/81 and 1981/82 breeding seasons. Adélies possess adaptations to harsh conditions and a short breeding season. They breed one month before chinstraps, lay two eggs, the first larger and heavier, and incubate for up to 14 days at a time. Chicks are brooded until aged c. 18 days, when they may form crèches, and fledge at c. 61 days. First hatched chicks grow faster than seconds. Chinstrap breeding is less constrained by environmental conditions. Their eggs are not dimorphic, parents incubate for up to 10 days at a time, chicks creche later, at c. 24 days and fledge earlier, at c. 53 days. Both chicks grow at the same rate. The diet of both species is mainly krill, though Adélies often catch more juvenile than adult krill, the latter probably being more available when chinstraps are breeding. Different feeding ranges, suggested by lower Adélie feeding frequencies, may also affect krill size caught. Feeding methods are probably similar. Krill rise to the surface at night, when both species probably feed, and 90 % of chinstrap foraging dives are to shallower than 45 m. Adult food consumption was equivalent to 600 g of krill per day, the fasting energy consumption c. 1.2 % of body weight per day and total estimated breeding energy consumption 1.7 - 2.0 x 105 kj. Lack of food for chicks was indicated, since chicks were less than c. 50 % of adult weight at fledging. This may have been due to the combined impact of the greatly increased penguin breeding population. Together, Adélies and chinstraps comprise over 85 % of the South Orkney avian biomass and are perhaps responsible for c. 80 % of krill consumption by birds.